Electronic Spectral Study and Thermodynamic Characterization of Doped Nd(III) Ions in various Semicarbazones - Jain, R.; Popli, A.; Tater, P.C.; Bhojak, N.; Soni, K.P. (Asian Journal of Chemistry, 2016)
The saturated organic ligand environment produced by various semicarbazones, around Nd(III) ion, has been studied with respect to hypersensitive transition involved in doped system. The various energy parameters such as Racah (Ek), Slater-Condon (Fk), Lande parameter (ζ4f) and the intensity parameters such as oscillator strength (P), Judd-Ofelt parameter (Tl) have been computed using partial and regression method. The bonding parameter (b½) and nephelauxetic ratio (b) have also been evaluated.